Comprehensive analysis of complete chloroplast genome sequence of Morina L. - Peng-Hui Liu; Qing Yuan; Huan Liu; Le-Le Qin; Yao Wei; Xu-Min Li; Fei Ren; Xiao-Lei Ma; Hai-Rui Liu (Scientific Reports)
Abstract In order to understand the structure characteristics of the chloroplast genome of Morina and explore the phylogenetic relationships within Morina, the whole chloroplast genomes of Morina chinensis and Morina kokonorica were sequenced in this study. Together with other two species of Morina which have been sequenced, the chloroplast genome structure of Morina was compared. Analysis of codon usage preference, analysis of the contraction and expansion of IR region, and comparison of the whole sequence were done. A total of 129 functional genes were annotated in M. chinensis and M. kokonorica chloroplast genome, with one more rpl23 gene than other 2 species. Tetranucleotide and pentanucleotide were only detected in M. chinensis. The ycf1 gene distributed in the SSC region in Morina longifolia, but on the IRa/SSC boundary of M. chinensis, M. kokonorica and Morina chlorantha genome. And the sequence of M. longifolia is the longest due to the extension of LSC and SSC. Phylogenetic analysis showed that the Morinoideae was an independent subfamily separated from Dipsacoideae and the relationship between Linnaeoideae and Morinoideae was closer. The divergence time between Morinoideae and Linnaeoideae was about 67.28 Ma and the divergence time of Morinoideae and Dipsacoideae was about 72.58 Ma. This study is conducive to the development and utilization of the resources of Morina, and provides a theoretical basis for the further study of this species.